Cognitive structuring of research articles in Philippine English - Mercado, Felixberto M. (2008)
Using the models of cognitive structuring in writing research articles proposed by Swales (1990;2004); Hopkins & Dudley-Evans (1988); and the genre analysis model of Bhatia (1993), the study analyzed and compared research articles (RAs hereafter) written in Philippine English and published in the Philippine Journal of Linguistics; Philippine Journal of Science; and Matimyas Matimatika. The study determined the underlying cognitive structuring and the optional and obligatory steps found in the moves of the cognitive structures of the I-M-R-D sections of research articles in linguistics, mathematics, and science written by Filipino professionals. The cognitive structuring of the RAs analyzed in this study is in conformity with the proposed models of cognitive structuring in terms of the moves and the linguistic exponents used in them. However, variations among the steps in each move were found across sections of RAs in linguistics, mathematics, and science written in Philippine English.
Includes bibliographical references (pages 39-40).